Meningkatkan Minat Belajar Anak Panti Asuhan Menara Kasih Indonesia Menggunakan Metode Tanyak Jawab Bersama Mahasiswi Kesejahteraan Sosial Fisip USU - Tampubolon, Sonang Martua; Triani, Emi; Ritonga, Fajar Utama (Yayasan Daarul Huda Kruengmane, 2025)
Students of the Social Welfare Study Program at FISIP USU conducted a community service activity at Menara Kasih Indonesia Orphanage, aiming to enhance the learning interest and motivation of the children.This activity was carried out using an interactive and participatory question-and-answer method. The method was chosen for its effectiveness in fostering two-way communication, improving material comprehension, and encouraging children to be more active and confident in the learning process. The results of the activity showed that the question-and-answer approach successfully created an enjoyable learning atmosphere, motivated children to ask questions and think critically, and increased their enthusiasm for learning. Therefore, this method can be considered an effective strategy to support both cognitive and emotional development of children living in orphanages.